2018
DOI: 10.1002/ece3.3869
|View full text |Cite
|
Sign up to set email alerts
|

Living in two worlds: Evolutionary mechanisms act differently in the native and introduced ranges of an invasive plant

Abstract: Identifying the factors that influence spatial genetic structure among populations can provide insights into the evolution of invasive plants. In this study, we used the common reed (Phragmites australis), a grass native in Europe and invading North America, to examine the relative importance of geographic, environmental (represented by climate here), and human effects on population genetic structure and its changes during invasion. We collected samples of P. australis from both the invaded North American and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 109 publications
(194 reference statements)
4
15
0
Order By: Relevance
“…Such populations may not be successful in highly productive wetlands in Europe dominated by P. australis (Ellenberg, ) where only competitive populations would survive. This is in accordance with the results of Guo, Lambertini, Nguyen, Li, and Brix (), Guo, Lambertini, Pyšek, Meyerson, and Brix () who showed that the populations invading in North America may have arrived on this continent preadapted from Europe and experience further postintroduction evolution in response to the new environment.…”
Section: Discussionsupporting
confidence: 92%
“…Such populations may not be successful in highly productive wetlands in Europe dominated by P. australis (Ellenberg, ) where only competitive populations would survive. This is in accordance with the results of Guo, Lambertini, Nguyen, Li, and Brix (), Guo, Lambertini, Pyšek, Meyerson, and Brix () who showed that the populations invading in North America may have arrived on this continent preadapted from Europe and experience further postintroduction evolution in response to the new environment.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the eco‐evolutionary history of nonnative populations is often too short to allow the populations to reach isolation by environment equilibrium (Guo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the demographic histories of nonnative populations are assumed to be more strongly influenced by stochastic elements than the demographic histories of native populations (e.g., due to more frequent founder events and population admixture; Verhoeven et al 2011). In addition, the eco-evolutionary history of nonnative populations is often too short to allow the populations to reach isolation by environment equilibrium (Guo et al 2018).…”
Section: Determinants Of Genetic Differentiationmentioning
confidence: 99%
See 2 more Smart Citations